2008
DOI: 10.2174/1874916x00802010043
|View full text |Cite
|
Sign up to set email alerts
|

The Curiosity-Arousing Function of Anti-Drug Ads

Abstract: Anti-drug ads may be designed to prevent illicit drug use, but might they also lead to a greater desire for experimenting with drugs? Priming theory suggests the ads could cause viewers to exaggerate drug use prevalence and expose gaps in viewers' experiential knowledge. By keeping the concept of adolescent drug use salient, anti-drug ads may trigger social comparison and make them wonder why drugs are so popular. Two studies explore such a possibility. Results from an initial between-participants experiment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Sample sizes ranged from 28 to 3608 (median: 284, IQR: 47–80). Three RCTs exposed individuals to marijuana-specific anti-illicit-drug PSAs,18 20 23 and four RCTs exposed individuals to a variety of anti-illicit-drug PSAs 16 19 21 22. Two RCTs reported positive effects of anti-illicit-drug PSAs corresponding to a −0.01 reduction in intention to use illicit drugs on a 1–7 scale of intention, and to a 0.06 increase in intention to call a drug-abuse hotline on a 1–5 scale of intention 16 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes ranged from 28 to 3608 (median: 284, IQR: 47–80). Three RCTs exposed individuals to marijuana-specific anti-illicit-drug PSAs,18 20 23 and four RCTs exposed individuals to a variety of anti-illicit-drug PSAs 16 19 21 22. Two RCTs reported positive effects of anti-illicit-drug PSAs corresponding to a −0.01 reduction in intention to use illicit drugs on a 1–7 scale of intention, and to a 0.06 increase in intention to call a drug-abuse hotline on a 1–5 scale of intention 16 18.…”
Section: Resultsmentioning
confidence: 99%
“…Our meta-analysis of RCTs demonstrated no significant benefit, and no studies reported any long-term effectiveness of these interventions. Importantly, most RCT and observational studies reported non-significant results, and three RCTs and one observational study found that anti-illicit-drug PSAs may have negative effects on anti-illicit-drug-use norms among targeted populations 4 19 20 22…”
Section: Resultsmentioning
confidence: 99%
“…Ads that use deliberate fear appeals may be risky as they may elicit psychological reactance from the viewers, which can reduce an ad’s effectiveness (Shoenbachler & Whittle, 1996). In fact, it has been suggested that by alarming the audience through portraying the proscribed behaviors, the PSAs may serve to normalize the unhealthy behavior, and promote competition and imitation from the audience (Wagner & Sundar, 1999) as audience “becomes curious, learns it is fun, or regards it as challenging” (Atkin, 2001, p.31). This is especially the case for high-risk adolescents (Atkin, 2001).…”
mentioning
confidence: 99%
“…20 This emphasis on fear-based deterrence, however, has been shown to negatively impact intentions to use drugs among PSA audiences. 21 This may arise as a result of exaggerated depictions of the prevalence of drug use depicted in PSAs, which may then expose gaps in viewers’ experiential knowledge of drugs. This, in turn, may arouse curiosity among viewers to experiment with drug use and lead to a weakening of protective social norms against their use.…”
mentioning
confidence: 99%
“…This, in turn, may arouse curiosity among viewers to experiment with drug use and lead to a weakening of protective social norms against their use. 21 The clear failure of such social marketing efforts, evidence in support of which has been generated by both independent experts 19 and government agencies, 22,23 belies a broader issue. Experts have posited that, because of the highly visible nature of these interventions, anti-drug social marketing interventions may have a secondary benefit in bolstering support for policies of drug criminalization through the mass media.…”
mentioning
confidence: 99%